Personality dimensions in chronic fatigue syndrome and depression. - Buckley, L; MacHale, S; Cavanagh, J; Sharpe, M; Deary, I; Lawrie, S (1999)
Chronic fatigue syndrome (CFS) is a poorly understood condition. Possible etiological factors include infectious agents, psychiatric disorders, and personality characteristics. We examined personality dimensions in 30 nondepressed patients with CFS, 20 patients with major depressive disorder (MDD), and 15 healthy controls. On the NEO-FFI, patients with CFS scored significantly lower than healthy controls on the extroversion subscale. On the neuroticism dimension of the Eysenck Personality Questionnaire (EPQ), patients with MDD scored higher than those with CFS, who in turn scored significantly higher than the healthy controls. CFS patients rated themselves as higher on neuroticism and less extroverted when ill than when they were well. Our results suggest that high scores on neuroticism and low scores on extroversion in CFS could be a reaction to chronic illness.